Intermittent Access to Ethanol Drinking Facilitates the Transition to Excessive Drinking After Chronic Intermittent Ethanol Vapor Exposure. (5th July 2017) - Kimbrough, Adam; Kim, Sarah; Cole, Maury; Brennan, Molly; George, Olivier
Abstract : Background: Alcohol binge drinking in humans is thought to increase the risk for alcohol use disorder (AUD). Unclear is whether drinking patterns (e.g., bingelike or stable drinking) differentially affect the transition to compulsive‐like drinking in dependent individuals. We examined whether chronic bingelike drinking facilitates the transition to compulsive‐like drinking in rats. Methods: Male Wistar rats were given 5 months of intermittent access to ethanol (EtOH) (IAE) or continuous access to EtOH (CAE) in a 2‐bottle choice paradigm. Then, rats were given chronic intermittent EtOH (CIE) vapor exposure. Escalation of EtOH intake and compulsive‐like responding for EtOH, using a progressive‐ratio schedule of reinforcement and quinine‐adulterated EtOH, were measured. Results: IAE rats escalated EtOH drinking after 2 weeks of 2‐bottle choice, whereas CAE rats exhibited stable EtOH drinking for 5 months. After 8 weeks of CIE, both IAE + CIE and CAE + CIE rats escalated their EtOH intake. However, IAE rats escalated their EtOH intake weeks sooner than CAE rats and exhibited greater EtOH intake. No differences in compulsive‐like responding were found between IAE + CIE and CAE + CIE rats. However, both IAE + CIE and CAE + CIE rats showed strong compulsive‐like responding compared with rats without prior IAE or CAE. Conclusions: Chronic EtOH drinking at stable or escalated levels for several months is associated with more compulsive‐like responding for EtOH in rats that are exposed to CIE compared with rats without a prior history of EtOH drinking. Moreover, IAE facilitated the transition to compulsive‐like responding for EtOH after CIE exposure, reflected by the escalation of EtOH intake. These results suggest that IAE may facilitate the transition to AUD. This study indicates that despite a moderate level of EtOH drinking, the IAE animal model is highly relevant to early stages of alcohol abuse and suggests that it may be associated with neuroadaptations that produce a faster transition to alcohol dependence. Abstract : In rats, 5 months of prior intermittent but not continuous access to ethanol facilitated the transition to excessive ethanol drinking during chronic intermittent ethanol vapor exposure. However, either 5 months of prior intermittent access to ethanol or continuous access to ethanol increased compulsive‐like ethanol drinking.